2018
DOI: 10.1080/09540121.2018.1503224
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing health among youth living with HIV using an iPhone game

Abstract: Background: Despite promising outcomes of antiretroviral therapy (ART), challenges to improving adherence among youth living with HIV (YLWH) exist. Mobile games are popular among youth and may improve skills related to resilience, coping, and ART adherence. This study examines the preliminary effects of an iPhone game/app on ART adherence, viral load, and relevant knowledge and attitudes among YLWH in Jackson, MS. Methods: A RCT with 61 YLWH tested the impact of BattleViro, an ART-related iPhone game, over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 39 publications
1
82
0
Order By: Relevance
“…An RCT conducted in the United States included 66 participants ages 14-26 years with a detectable VL at baseline and evaluated an iPhone game designed around themes of 'fighting' or 'destroying' HIV in the body by taking ART. After 16-weeks, among participants who had newly initiated ART, the decrease in mean log VL of participants in the intervention arm (3.63-0.93) was significantly greater than the decrease in mean log VL of participants in the control arm (3.94-1.53) (p = 0.04) [61].…”
Section: Additional Studies In High Income Countriesmentioning
confidence: 75%
See 1 more Smart Citation
“…An RCT conducted in the United States included 66 participants ages 14-26 years with a detectable VL at baseline and evaluated an iPhone game designed around themes of 'fighting' or 'destroying' HIV in the body by taking ART. After 16-weeks, among participants who had newly initiated ART, the decrease in mean log VL of participants in the intervention arm (3.63-0.93) was significantly greater than the decrease in mean log VL of participants in the control arm (3.94-1.53) (p = 0.04) [61].…”
Section: Additional Studies In High Income Countriesmentioning
confidence: 75%
“…Some interventions implemented in a high income setting improved outcomes among adolescents and youth [58][59][60][61] and may be feasibly adapted for use in resource-limited settings. Those utilizing social media or smart phone applications show promise given rapidly increasing access to internet and mobile phones among young people in LMICs [74].…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies have demonstrated improved adherence with mobile games, web-based interventions, interactive text message reminders, and mindfulness interventions in the US ALWHIV. [17][18][19][20] Several additional studies investigating novel approaches for ALHIV engagement in care are ongoing. [21][22][23][24] These interventions should be studied in pregnancy as well.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral theories, conceptual models for game development, and playtesting are known to improve the effectiveness of serious games [ 30 , 31 ]. There is limited evidence available about the use of specific theoretical frameworks to guide the game development process for medication safety–focused games for youth [ 29 , 32 ].…”
Section: Introductionmentioning
confidence: 99%